CASO 5-2015: Cryptogenic organizing pneumonia - Sibaja Campos, Mario (2015)
Cryptogenic organizing pneumonia (COP) is a distinct histopathologic entity characterized byMasson bodies which are intraalveolar buds of granulation tissue; consisting of connective tissue and myofibroblasts. This pathologic pattern when present with the characteristic imaging and clinical features of COP defines the diagnosis of the disease. A specific etiology is not found. Treatment with corticosteroids results in a rapid clinical and imaging improvement but unfortunately relapses are common upon decreasing the dose or stopping the treatment. This case report describes a typical case of COP with the characteristic improvement with corticosteroid therapy and relapse upon treatment taper